Role of Cognitive Biases in Understanding Financial Investment Behavior - Mandal, Chanchal; Riyat, Sonia (Indian Journal of Research in Capital Markets, 2024)
Purpose : The main goal of this paper was to examine the many emotional biases and how they affected the way that people invest. Furthermore, it highlighted the importance of comprehending the impact of diverse affective prejudices to assist investors in making well-informed choices. Methodology : The study identified six different forms of cognitive biases, including endowment, status quo, regret aversion, self-control, optimism, and overconfidence (illusion of knowledge). It also evaluated the influence of each type of bias on overall investment behavior. Findings : The purpose of the suggested paper was to investigate how various emotional biases affected investors’ lives when they made rational financial decisions. It also conducted an experiential analysis of previous research papers on cognitive biases to gain a deeper understanding of the significance of various biases and how they affected individual investors’ decision-making. Practical Implications : It has been repeatedly noted that mental biases help investors make judgments about their investments by serving as a compass in a variety of economic contexts. To optimize returns and demonstrate appropriate investment conduct, investors must be well-informed, logical, and not overly critical. They should also follow their own gut feelings and beliefs. Originality : The purpose of the current study, according to the literature analysis, was to understand investor behavior in the securities markets and the effects of that activity.